2014
DOI: 10.1111/neup.12141
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory amino acid transporter 2 downregulation correlates with thalamic neuronal death following kainic acid‐induced status epilepticus in rat

Abstract: Recurrent seizures without interictal resumption (status epilepticus) have been reported to induce neuronal death in the midline thalamic region that has functional roles in memory and decision-making; however, the pathogenesis underlying status epilepticus-induced thalamic neuronal death is yet to be determined. We performed histological and immunohistochemical studies as well as cerebral blood flow measurement using 4.7 tesla magnetic resonance imaging spectrometer on midline thalamic region in Sprague-Dawle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…A rat model of cerebral KA injection-induced SE was employed to further investigate the mechanisms responsible for epileptic disease and antiepileptic drugs in the previous studies [18][19][20]. In the current study, using the same rat model our data showed that HIF-1α was significantly increased in the specific brain regions such as the parietal cortex, hippocampus and amygdala 1-7 days after induction of SE by cerebral KA injection (Fig.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…A rat model of cerebral KA injection-induced SE was employed to further investigate the mechanisms responsible for epileptic disease and antiepileptic drugs in the previous studies [18][19][20]. In the current study, using the same rat model our data showed that HIF-1α was significantly increased in the specific brain regions such as the parietal cortex, hippocampus and amygdala 1-7 days after induction of SE by cerebral KA injection (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…In this report, a rat model of cerebral KA injection-induced SE [18][19][20] was employed and we also determined the effects of inhibiting HIF-1α on the levels of PICs in the parietal cortex, hippocampus and amygdala. Moreover, we examined the effects of inhibiting of HIF-1α and TNF-α receptor on protein expression of an indicator of cell apoptosis Caspase-3 in those specific brain regions of epileptic rats.…”
Section: Introductionmentioning
confidence: 99%
“…The use of animal models, on the other hand, has so far demonstrated equivocal results on the regulation of GLT1 expression in epilepsy. Downregulation (Samuelsson et al 2000; Ueda et al 2001; Lopes et al 2013; Sakurai et al, 2015), upregulation (Simantov et al 1999), or no change (Miller et al 1997) in GLT1 have all been reported in a variety of epilepsy models. These differences, however, can be accounted for by several factors, including mRNA vs .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Sakurai et al (2015) demonstrated that neuronal cell death was associated with a focal loss of GLT1 immunoreactivity and stronger immunoreactivity for glutamate (Sakurai et al, 2015). In addition, Murphy-Royal et al (2015) found that although GLT1 is anchored to the membrane at synapses, it can be untethered after glutamate release and can undergo rapid, activity-regulated surface diffusion between synaptic and non-synaptic sites to ensure effective glutamate clearance (Murphy-Royal et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Thirty‐six rats were subjected to intraperitoneal injection of KA (5 mg/mL in saline, 10 mg/kg; Sigma‐Aldrich, St. Louis, MO, USA) to induce status epilepticus (SE), and 15 animals were treated with the same volume of normal saline solution (Otsuka Seiyaku, Tokyo, Japan) as controls. According to our previous report, we judged behavioral scale stage 4 (proposed by Zhang and colleagues) as induction of generalized seizure, and SE was considered as a condition with recurrent generalized seizure that lasts at least 30 min based on the International League Against Epilepsy task force report . The rats having SE were kept for 0 day (5 h after KA injection; n = 5), 7 (n = 8) and 14 days ( n = 8).…”
Section: Methodsmentioning
confidence: 99%